Pengaruh Model Outdoor Learning terhadap Pembelajaran Menulis Cerpen oleh Siswa Kelas IX SMP Negeri 2 Pematangsiantar - Via Deboris Purba; Jumaria Sirait; Martua Reynhat Sitanggang Gusar (Medan Resource Center, 2022)
This study aims to determine the effect of the Outdoor Learning model on learning to write short stories by class IX students of SMP Negeri 2 Pematangsiantar. This study uses a quantitative experimental method with a pre-experimental type using a one-group pretest-posttest design. The sample in this study were students of class IX-10, totaling 29 students. The sampling used in this research is purposive sampling. The data collection technique used is the short story writing test technique for students' short story writing activities. The results of the research on writing short stories before using the outdoor learning model reached an average value of 58.93 in the sufficient category. Meanwhile, the results of the research on writing short stories after using the outdoor learning model reached an average value of 78.37 in the good category. Based on the results of the pretest and posttest, there are differences in the results of writing short stories with a tcount of 13.04 with a significant level of 5% = 0.05 at db = 28, a ttable of 1.701 is obtained. Thus, tcount = 13.04 < 1.701, so it can be concluded that H0 is rejected and H? is accepted, meaning that there is an effect of using the outdoor learning model on the ability to write short stories for class IX students of SMP Negeri 2 Pematangsiantar.